PENGARUH PENERAPAN EXPERIENTIAL MARKETING STRATEGIC TERHADAP KEPUASAN KONSUMEN DI FIGURE OF JAVA ADVENTURE TUBAN - Martha Laila Arisandra (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2018)
This study examines the effect of experiential marketing strategic implementation on customer satisfaction in Figure of Java Adventure Tuban. Consumers studied are PAUD teachers, PG, TK, INSTANSI who are partners of FIGURE OF JAVA ADVENTURE TUBAN and order products offered FIGURE OF JAVA ADVENTURE TUBAN. This research is done because now there has been a shift from traditional marketing to experiential marketing. The purpose of this study is to determine the effect of Experiential Marketing Strategic implementation on customer satisfaction either partially or simultaneously. The six free variables in this study include communication, visual identity, product presence, brand cooperation, spatial environment, and people. The hypothesis that the authors formulated in this study is that the Experiential Marketing strategy that has been done by FIGURE OF JAVA ADVENTURE influential both partially and simultaneously to customer satisfaction. The analytical tool used is with multiple linear regression model with the help of SPSS 22 for windows program. Hypothesis testing using t test and F test, both at 5% significant level. The results show that the six independent variables, namely communication, visual identity, product presence, brand cooperation, spatial environment, and people partially and simultaneously have a significant effect on customer satisfaction. Based on the results of the analysis, should the FIGURE OF JAVA ADVENTURE continue the existing Experiential Marketing strategy, it is better FIGURE OF JAVA ADVENTURE to improve innovation, arrangement of existing games so that consumers feel there is something new, add variety of products with always pay attention to the taste and desire so that more consumers will become partners of FIGURE OF JAVA ADVENTURE, improve the quality of service especially FIGURE OF JAVA ADVENTURE in serving customers, more offers more varied advertising for consumers to prevent advertising wearout and make the site about FIGURE OF JAVA ADVENTURE to support FIGURE OF JAVA ADVENTURE promotion activities to be recognized by the wider community.